Relationships Between Life Values, Peculiarities of Students’ Activity and Career Orientation - Lesin, Alexander; Fomina, Natalya (East European Journal of Psycholinguistics, 2015)
This article deals with modern young people’s life values which constitute the basis of orientation and determine the vector of personality development. The authors, emphasizing high demands placed on individuals and their expertise in various areas of life by modern society, underline the necessity to thoroughly investigate the value-sense sphere as one of the main components of personality orientation and activity which determines a man as the subject of life. Different groups of values are revealed: terminal and instrumental, abstract and concrete, external and internal. Special consideration is given to the importance of forming students’ personality as the most socially active group of the young generation and to the possibility for diagnosing peculiarities of speech personality on the basis of analyzing speech that is closely connected with thinking and that represents the process of using the language for conveying and comprehending certain sense. Based on the results of the research conducted with the use of various methodologies, including analysis of speech activity products, it is concluded that students have different groups of values that are dominating. Relationships are revealed between general number of values, as well as terminal and instrumental, abstract and concrete, external and internal students’ values and between peculiarities of initiative, that characterize such an integral aspect of personality as activity, and career orientation. Possibilities of speech diagnosis of personality value system are demonstrated. Conclusions are drawn about the necessity of harmonizing students’ value sphere with the view of successfully realizing their potential in career and personal life. Knowing and taking into account relationships between them, which are revealed and presented in the article, can help psychologists and teachers maintain effective psychological-pedagogical process of their professional training at the university, the essential component of which is developing personality of future experts, and also can help students themselves on their way to self-actualization, self-development, self-improvement and self-fulfillment.ReferencesLesin A., Fomina, N. (2014). Svyaz napravlennosti lichnosti i konflikta tsennosteystudentov [Relationship between students’ personality orientation and value conflict]. In:S. Boldyreva (Ed.) Youth, Family, Society: Proceedings of the International Scientific Conference(pp. 71–74). Ryazan: Ryazan Branch of Moscow Psychological and Social University.Karelin, A. (2007). Bolshaya Entsiklopediya Psihologicheskih Testov [GreatEncyclopedia of Psychological Tests]. Moscow: Eksmo.Krupnov, A. (2008). Sistemno-dispozitsionnyiy podhod k izucheniyu lichnosti i eesvoystv [The system-dispositional approach to studying the personality and its traits]. The Bulletinof Peoples’ Friendship University of Russia, 1, 63–74.Leontyev, D. (1992). Metodika Izucheniya Tsennostnyh Orientatsiy [Methodology forStudying Value Orientations]. Moscow: Smysl.Fomina, N. (2002). Svoystva Lichnosti i Osobennosti Rechevoy Deyatelnosti [PersonalityTraits and Peculiarities of Speech Activity]. Ryazan: Uzorochye.Lesin, A., Fomina, N. (2014). Tipy napravlennosti lichnosti i osobennosti tsennostnyihorientatsiy studentov [Types of personality orientation and peculiarities of students’ value system].Alma Mater (Bulletin of High School), 4, 34–38.Motkov, O. (2005). Kak ustroena lichnost [The Nature of Personality]. Moscow: LevVygotsky Institute of Psychology.